X-Ray Spectra from General Relativistic Radiation Magnetohydrodynamic Simulations of Thin Disks - Nathaniel Roth; Peter Anninos; P. Chris Fragile; Derrick Pickrel (The Astrophysical Journal)
We compare X-ray emission from several general relativistic, multifrequency, radiation magnetohydrodynamic simulations of thin black hole accretion disks with different accretion rates and spins. The simulations were performed using the M _1 closure scheme, resolved with 12 frequency (energy) bins logarithmically spaced from 5 × 10 ^−3 to 5 × 10 ^3 ​​​ keV. We apply a general relativistic Monte Carlo transport code to postprocess the simulation data with greater fidelity in frequency resolution and Compton scattering treatment. Despite the relatively few energy bins and Kompaneets approximation to Compton scattering utilized in the M _1 method, we find generally good agreement between the methods. Both produce prominent thermal profiles with peaks around 2–2.5 keV, where agreement is particularly strong and representative of the soft state. Both also find weaker (lower-luminosity) thermally sourced emission extending out to 100 keV due to the hotter innermost regions of the disks. Inverse Compton scattering becomes increasingly effective at hardening spectral outputs with increasing black hole spin, and becomes the dominant mechanism for photons that escape with energies between 10 to several hundred keV. At very high rates of spin, the radiation flux in this upscattered component becomes comparable to the thermal flux, a phenomenon typically associated with intermediate states. Beyond 10 ^4 keV, we observe faint, free–free emission from hot, optically thin coronal regions developing near the horizon, common to both spinning and nonspinning black holes.